Mengapa Proyek Perangkat Lunak Gagal (Penerapan Manajemen Resiko dalam Proyek Perangkat Lunak) - Yasmi Afrizal (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2010)
The greater and problems complex of software development project enables the event of failure. Risk management is an approach to guide minimization or lessens the failure impact. This paper is explain risk management modelbase that probe event risk in developing software. Risk management has step of solution consisted of by identification, analysis, mitigation strategy risk. This paper also very useful to assist academician, researcher and practitioner to be more understanding risk management as one part of the software engineering.